Root coverage stability: A systematic overview of controlled clinical trials with at least 5 years of follow‐up - Kristina Bertl; Loukia M. Spineli; Khalid Mohandis; Andreas Stavropoulos (Wiley, 2021)
Abstract Objectives To systematically assess the long‐term outcome (≥5 years) of root coverage procedures reported in controlled clinical trials. Material and Methods Literature search was performed according to the PRISMA guidelines with the following eligibility criteria: (a) English or German language; (b) controlled (CT) or randomised controlled clinical trials (RCT); (c) root coverage procedure with ≥5 years follow‐up; and (d) clinical treatment effect size and/or patient‐related outcome measures (PROMs) reported. Results Four CT and 14 RCT with a follow‐up of 5-20 years fulfilled the eligibility criteria; sample size per study ranged from 8 to 70 patients contributing with 18-149 sites. Coronally advanced flap (CAF) and CAF + connective tissue graft (CTG) were the prevalent treatments (i.e., in 24 and 38% of the groups, respectively), while other flap designs and adjuncts (i.e., enamel matrix derivative, bone graft, collagen membrane) were represented only once. For single Miller class I/II gingival recessions (GR), CAF + CTG appeared advantageous compared to other techniques, and provided low residual recession depths (i.e., ≤0.5 mm), and complete root coverage in ≥2/3 of the patients; similar tendency was observed for multiple GR. No data on Miller class III/IV GR is available. No meta‐analysis was feasible due to lack of similarity in the clinical and methodological characteristics across the trials and observed comparisons of interventions. Conclusions CAF + CTG appears to be the 'gold standard' technique for the treatment of single and multiple Miller class I/II GR also in regard to long‐term (i.e., ≥5 years of follow‐up) treatment outcomes. There is little information regarding the performance, on the long‐term, of other techniques and adjuncts.